FACTORS ASSOCIATED WITH FAILURE TO QUIT SMOKING AMONG SMOKING CESSATION CLINIC ATTENDEES IN MALAYSIA - Ismail, Halim; Mohamed Hanan, Mohd Fathulzhafran; Mohd Yusoff, Hanizah; Bhuvanendran Pillai, Anaanthan (Malaysian Journal of Public Health Medicine, 2023)
Tobacco smoking is a major public health concern because it is a contributing risk factor of non-communicable diseases. Smoking cessation clinics are an intervention provided by the Ministry of Health Malaysia to help smokers quit smoking. We investigated the characteristics of the attendees of these clinics and the factors contributing to failure to quit smoking among the attendees in a primary health care setting in Malaysia. This was a cross-sectional study using retrospective secondary data from 245 attendees of smoking cessation clinics in the district of Hulu Langat, Malaysia from 2016 to 2017. Purposive sampling was used, and data were analysed using SPSS 22.0. Failure to quit smoking was defined as failure to abstain from tobacco smoking after at least 6 months’ attendance at the smoking cessation clinic. The majority of attendees were middle-aged, male, Malay, had at least secondary school education and were married. The quit smoking failure rate was 61.2%. The factors associated with failure to quit smoking were the clinic attended, being non-Malay, smoking more cigarettes per day, fewer attempts to quit, fewer visits and higher addiction level. The logistic regression model showed that non-Malays and those with higher modified FTND (Fagerström Test for Nicotine Dependence) scores were 49.6 times and 16.2 times more likely to fail, respectively, while smoking for >15 years had a lower failure rate. Emphasis should be placed on non-Malay smokers and smokers with higher FTND scores for better quit smoking outcomes.